Bioactive silver(I) complex delivered via bacterial cellulose and Zeolitic imidazolate framework-8 composites for skin cancer therapy - Silmara C. Lazarini Frajácomo; Augusto Henrique Piva; Hernane da Silva Barud; Eliane Trovatti; Tamires de Souza Nossa; Bernardo Castro-Dominguez; Regina Celia Galvão Frem; Bruna C. Lustri; Douglas H. Nakahata; Pedro P. Corbi; Wilton R. Lustri (Cellulose, 2026)
Abstract Topical antimicrobial strategies that combine targeted drug delivery with selective cytotoxicity are critically needed for treating infected skin lesions, especially those complicated by multidrug-resistant bacteria. Here, we report the synthesis, characterization, and evaluation of a silver(I) complex with the sulfonamide probenecid (Ag–PROB) and its integration into a bacterial cellulose (BC) based composite with zeolitic imidazolate framework-8 (ZIF-8) for controlled release applications. We developed two delivery platforms, Ag–PROB@BC and Ag–PROB@BC/ZIF-8, with the latter incorporating the metal–organic framework, and assessed their antimicrobial and antitumor activities. Ag–PROB demonstrated potent, selective in vitro cytotoxicity against a panel of tumor cell lines, including pulmonary adenocarcinoma (A549, GI 50 = 35.77 μmol L −1 ) and murine melanoma (B16, GI 50 = 35.77 μmol L −1 ), with minimal effects on non-tumorigenic cells (e.g., HUVEC, GI 50 = 202.06 μmol L −1 and Hakata, GI = 249.16 μmol L −1 ). Both delivery systems showed sustained release in disk diffusion and Franz cell tests, with no observed DNA interaction, and in vivo toxicity was confirmed in Tenebrio molitor larvae. The Ag–PROB@BC/ZIF-8 composite displayed improved release profiles, providing a versatile platform for topical antimicrobial and antitumoral therapy. Our findings highlight a synergistic approach that combines metal-based therapeutics, bio-derived scaffolds, and ZIF-8 to create advanced multifunctional materials for skin cancer treatment.